2012 XXth International Conference on Electrical Machines 2012
DOI: 10.1109/icelmach.2012.6350116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrical steel grade on the temperature distribution in direct-drive PM synchronous generators for 5 MW wind turbines

Abstract: The effect of the magnetic and thermal properties of 4 electrical steel grades were compared for a Permanent Magnet Synchronous Generator (PMSG). The low loss grades are expected to have less iron loss in the stator lamination, but their thermal conductivity may be lower. Therefore, the evacuation of the heat may be less effective. This has an influence on the temperature distribution, which is crucial in case of PMSG. The investigated generator is a 5 MW, radial flux machine designed for direct drive wind tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In [27], Kowal et al investigated the relationship between the thermal conductivity of materials and their electromagneticthermal performance and demonstrated that the thermal conductivity of steel has an influence on the temperature distribution. In order to reasonably simplify the thermal analysis, it is assumed that different heat sources (losses) are distributed uniformly in the corresponding heating elements and the calculated thermal nodes is located at the centre of the heat elements.…”
Section: A Thermal Conduction Resistancementioning
confidence: 99%
“…In [27], Kowal et al investigated the relationship between the thermal conductivity of materials and their electromagneticthermal performance and demonstrated that the thermal conductivity of steel has an influence on the temperature distribution. In order to reasonably simplify the thermal analysis, it is assumed that different heat sources (losses) are distributed uniformly in the corresponding heating elements and the calculated thermal nodes is located at the centre of the heat elements.…”
Section: A Thermal Conduction Resistancementioning
confidence: 99%
“…In [27], Kowal et al investigated the relationship between the thermal conductivity of materials and electromagnetic-thermal performance and demonstrated that the thermal conductivity of steel has an influence on the temperature distribution. In order to simplify the thermal analysis reasonably, the assumption that different heat sources (losses) distribute in the corresponding heating elements uniformly and the calculated thermal nodes locates at the centre of heat elements.…”
Section: A Thermal Conduction Resistancementioning
confidence: 99%